Impacto de diferentes testes de avaliação funcional sobre o sistema cardiorrespiratório e subjetivo de mulheres obesas: implementando recursos em protótipo para avaliação funcional - Luporini, Luciana Di Thommazo (2015)
Obesity is considered a worldwide epidemic, with high prevalence in females. It is associated to increased mortality rates due to adverse consequences, such as cardiovascular and metabolic diseases. In addition, obese individuals show impaired cardiorespiratory fitness and functional capacity. In this context, we have proposed two observational and cross-sectional studies that could contribute to the understanding the cardiovascular, metabolic, ventilatory, and perceptual responses in this population to different exercise tests, such as the maximum cardiopulmonary test (CPX), considered the gold standard assessment for cardiorespiratory fitness, as well as functional field tests, which were less expensive and more similar to daily activities, such as the six-minute walk test (6MWT), incremental shuttle walk test (ISWT), and the six-minute step test (6MST). Moreover, we have proposed an innovative step ergometer, which provides a performance recorder and a software for following the user´s progression. The first study é entitled "Are cardiovascular and metabolic responses to field walking tests interchangeable and obesity-dependent?". Aimed to investigate if the physiological responses to the ISWT and 6MWT were in agreement with those obtained in CPX and determine if the submaximal tests could be interchangeable in obese women and controls. Fifty one obese women were evaluated (ObG) and 21 controls (CG) through clinical evaluation, CPX, ISWT and 6MWT. There was agreement between CPX and both the 6MWT [oxygen uptake (VO2, mL•kg-1•min-1) = 6.9 (CI: 5.7-8.1), and heart rate (bpm) = 37.0 (CI: 33.3-40.7)] and ISWT [VO2 (mL•kg-1•min-1) = 6.1 (CI: 4.9-7.3), and heart rate (bpm) = 36.2 (CI: 32.1-40.3)]. We found similar cardiovascular and metabolic responses to both tests in the ObG but not in the CG. Strong correlations were demonstrated between 6MWT and ISWT variables: VO2 (r=0.70); dyspnea (r=0.80); and, leg fatigue (r=0.70). The 6MWT and the ISWT may both hold interchangeable clinical value when contrasted with CPX in obese women and may be a viable alternative in the clinical setting when resources and staffing are limited. The second study was entitled "Six-minute step test as a predictor of cardiorespiratory fitness in obese women" and aimed to assess the 6MST accuracy to determinate cardiorespiratory fitness (CRF) and its ability to predict xiii peak oxygen uptake (VO2) and heart rate (HR) achieved during CPX in sedentary obese women. Fifty-six sedentary obese women underwent clinical evaluation, CPX and 6MST. There was a satisfactory concurrent validity between the CPX and 6MST, with a mean difference of 5.1±3.6 mL•kg-1•min-1 and 23±13 bpm in relation to peak VO2 and HR, respectively. The 6MST demonstrated moderate accuracy in predicting CPX responses (area under the curve: 0.72, 95% CI: 0.59 - 0.83). The number of step cycles and peak HR during the 6MST explained 31% and 39% of the total variance in peak VO2 and HR obtained during CPX, respectively. We conclude that the 6MST is accurate to discriminate obese women with an adequate CRF from women with a poor status and it can predict metabolic and cardiovascular maximal exercise values, as well as it may be a valid means of assessing CRF in sedentary obese women, particularly in clinical settings where space and resources are limited. The third study is related to a proposal of a innovative utility model registered in the Instituto Nacional de Propriedade Intelectual, in Brazil, as a patent and is entitled "constructive provision introduced in portable exercise step with performance recorder and software." The exercise step aims to fill a gap in the current trade showing improvements over currently available steps, regarding performance, usability, cost, portability, maintenance, safety and ergonomics. Financial support: Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq 141331/2011-9), Brasília, DF, Brasil; and, Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP 2009/01842-0).